Balanced science 2 - Jones,Geoff; Jones, Mary.; Marchington, Phillip; Acaster, David (New York : Cambridge University Press, 1994)
This two-volume text is designed to meet the requirements of the National Curriculum (Y10 and Y11 students) and the Double Award National Criteria for Balanced Science, and is suitable for integrated, co-ordinated and combined science courses.
Includes index.
Keywords: science